Nilai Integrasi Islam pada Mata Kuliah Keterpaduan Islam dan Sains - Eko Wahyu Nur Sofianto; Ratna Kartika Irawati (Global Perspectives in Education Journal, 2025)
This study explores the contextual integration of Islamic values within science education through the "Islam and Science Integration" course in an Islamic higher education institution. Using a qualitative case study approach, the research involved five students from the Physics Education Study Program at Universitas Islam Negeri Antasari Banjarmasin. Data were collected through interviews and documentation, and analyzed using data reduction, data display, and conclusion drawing. The findings reveal that students demonstrate Islamic integration by applying fiqh principles to contemporary scientific and technological issues. However, integrating Islamic values with science does not override fiqh rulings rooted in the Qur'an and Sunnah. Instead, this integration enriches students' contextual understanding of religion and science. The study concludes that the value of Islamic integration in science education is best reflected in the fiqh framework, offering a meaningful model for harmonizing religious understanding with scientific reasoning. This research contributes to developing context-based Islamic science education in higher education.